Savings Adequacy Uncertainty: Driver or Obstacle to Increased Pension Contributions? - Ron J.G. van Schie; Bas Donkers; Benedict G.C. Dellaert (Tinbergen Institute, 2012)
Deciding how much to save for retirement is a difficult task that includes many uncertainties. In this paper, we use data from a representative Dutch household panel to study the impact of uncertainty regarding one's savings adequacy on retirement savings contributions and information search processes. We combine ideas from the literature in psychology and economics that provide opposing predictions regarding the impact of uncertainty on retirement savings contributions. Our results indicate that the effect of uncertainty is moderated by two factors: an individual's perceived adequacy of current savings and that individual's financial constraints. In particular, we find that uncertainty increases retirement contributions for those who believe that they save adequately; however, it hinders retirement contributions for those who believe that they save inadequately. This effect of uncertainty is further moderated by the availability of financial means: a reduction in uncertainty results in greater contributions to savings only when financial constraints are absent. We also find that uncertainty has both indirect and direct effects on savings information search. In particular, uncertainty indirectly affects savings information search because it impacts individuals' intentions to save, which consequently forces individuals to engage in purchase-oriented information search; however, uncertainty also has a direct effect because individuals engage in ongoing information search processes to directly reduce uncertainty. The implications of these findings are discussed.
urn:NBN:nl:ui:15-1765/32658
Keywords: D14; D83; D91; M38; 330; uncertainty; savings adequacy; retirement; financial decision making; Altersvorsorge; Sparen; Privater Haushalt; Entscheidung bei Unsicherheit; Niederlande